BTEX recovery from waste rubbers by catalytic pyrolysis over Zn loaded tire derived char. (15th July 2021) - Pan, Yuhan; Sima, Jingyuan; Wang, Xinwen; Zhou, Yonggang; Huang, Qunxing
Graphical abstract: Highlights: Tire derived char (TDC) was used as catalyst during pyrolysis treatment of waste tire. TDC was catalytically effective for the promotion of BTEX generation. Loading of additional Zn enhanced the catalytic performance of TDC. The total yield of BTEX increased by 5.95 times at the optimal experimental condition. A low-cost and high-performance carbon-based catalyst was developed. Abstract: Recovering valuable chemicals (BTEX: Benzene, toluene, ethylbenzene, and xylene) via catalytic pyrolysis of waste tires is a promising and sustainable approach. Zinc loaded tire derived char (TDC) was used as cheap catalyst for recovering valuable BTEX products from waste tire through pyrolysis in this study. The catalytic capability of TDC on BTEX production were experimentally investigated with respect to Zn content, catalytic temperature, and catalyst-to-tire ratio. Due to the abundant acid sites on the surface, the TDC showed notable catalytic capability for improving BTEX yield which was 2.4 times higher than that from uncatalyzed case. The loading of additional Zn increased the acid sites on the TDC and the catalytic performance was further improved. The increase of catalytic temperature and catalyst-to-tire ratio favored the formation of BTEX, but it also brought undesirable consequences, such as the mass loss of tire pyrolysis oil (TPO) and the formation of polycyclic aromatic hydrocarbons. The optimal TPO products were obtained at 600 °C with catalyst-to-tire ratio of 20. At this condition, the relative content of BTEX reached 54.70% and the cumulative BTEX yield was 10.13 wt%, increasing by 5.95 times compared to that of non-catalytic condition. This work provided a novel strategy of replacing traditional expensive catalysts with low-cost and effective carbon-based materials in the field of catalytic pyrolysis of waste tires.